Galacto-oligosaccharides as infant prebiotics: production, application, bioactive activities and future perspectives. Issue 6 (28th February 2023) - Ambrogi, Valentina; Bottacini, Francesca; Cao, Linqiu; Kuipers, Bas; Schoterman, Margriet; van Sinderen, Douwe
Abstract: Galacto-oligosaccharides (GOS) are non-digestible oligosaccharides characterized by a mix of structures that vary in their degree of polymerization (DP) and glycosidic linkage between the galactose moieties or between galactose and glucose. They have enjoyed extensive scientific scrutiny, and their health-promoting effects are supported by a large number of scientific and clinical studies. A variety of GOS-associated health-promoting effects have been reported, such as growth promotion of beneficial bacteria, in particular bifidobacteria and lactobacilli, inhibition of pathogen adhesion and improvement of gut barrier function. GOS have attracted significant interest from food industries for their versatility as a bioactive ingredient and in particular as a functional component of infant formulations. These oligosaccharides are produced in a kinetically-controlled reaction involving lactose transgalactosylation, being catalyzed by particular β-galactosidases of bacterial or fungal origin. Despite the well-established technology applied for GOS production, this process may still meet with technological challenges when employed at an industrial scale. The current review will cover relevant scientific literature on the beneficial physiological properties of GOS as a prebiotic for the infant gut microbiota, details of GOS structures, the associated reaction mechanism of β-galactosidase, and its (large-scale) production.